RATIO LEGIS PRZEDAWNIENIA - Pałdyna, Tomasz (Zeszyty Prawnicze, 2017)
Ratio legis of Limitation of Claims Summary A common element of the works on limitation of material claims is the analysis of its justification. This has its reasons: limitation of claims evokes serious doubts of ethical nature. It often happens that the protection is rejected to an entitled person, even in a situation when the debtor confirms his obligation, claiming at the same time the lapse of the period of prescription. Due to this, objections are formulated that limitation of claims authorises immoral behaviours, undermines the validity of law, weakens the role of law in a society, infringes the rule of law as well that it collides with a common sense of justness and the logic of the protection of exclusive rights. Notwithstanding the above limitation of claims exists in almost all civil law systems, therefore, it seems to be justifiable. The reasons for introducing this legal means into the system of civil law are discussed in this paper. The aim of limitation of claims is the protection of the defendant in the proceedings because of the difficulties with presenting evidence for a claim which came into being many years before. Retaining such claims is contrary to the interests of the court system because the proceedings initiated after many years could lead to accidental verdicts. Moreover maintaining a certain status may create its legality due to the principle of security of law. Furthermore, delayed persuing claims may be a form of earning money out of the statute interest with high interest rates, which is not desirable. The analysis presented in this paper allows a conclusion that limitation of claims has mammy functions: protective, cleansing, stabilising and animating. The proposed division is of an arranging nature as it stresses the main functions of limitation of claims and its role in trade.